A network analysis of the non-fungible token (NFT) market: structural characteristics, evolution, and interactions - Sajjad Alizadeh; Amin Setayesh; Arash Mohamadpour; Behnam Bahrak (Applied Network Science, 2023)
Abstract Non-fungible tokens (NFTs) are a type of digital asset that can prove ownership of both virtual and physical assets using blockchains. Even though creating and trading NFTs have experienced a significant increase, research on the NFT market and its features is limited. In this study, we aim to bridge this gap by conducting a comprehensive analysis on the NFT market and its evolution from a network perspective. We examined the transactions network between NFT buyers and sellers and analyzed the structural characteristics of the NFT trades network. Additionally, we looked at how NFT usage and transactions have changed over time. Our findings indicate that a few participants are responsible for most of the NFT sales and purchases, while the majority of the addresses have only a few NFT transactions. Furthermore, we investigated the structural properties of the NFT trades network, including centrality measures, clustering coefficient, and assortativity, and how they have changed over time. We also explored the interactions between NFTs by constructing a graph of NFT relations. We identified four major communities and highlighted the top NFT projects in each community. We also examined the NFT projects that buyers mostly purchase together.